2003
DOI: 10.1113/jphysiol.2002.035915
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Exchange Profile in Rat Muscles of Contrasting Fibre Types

Abstract: To determine whether fibre type affects the O2 exchange characteristics of skeletal muscle at the microcirculatory level we tested the hypothesis that, following the onset of contractions, muscle comprising predominately type I fibres (soleus, Sol, 86 % type I) would, based on demonstrated blood flow responses, exhibit a blunted microvascular PO2 (PO2,m, which is determined by the O2 delivery (Q̇O2) to O2 uptake (V̇O2) ratio) profile (assessed via phosphorescence quenching) compared to muscle of primarily type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
178
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(191 citation statements)
references
References 56 publications
13
178
0
Order By: Relevance
“…Indeed, previous studies have shown that NO 3 Ϫ supplementation can increase muscle blood flow in the running rat (24) and that NO 2 Ϫ infusion can increase blood flow in humans performing forearm exercise (16). The potential for enhanced perfusion with BR is likely to be more pronounced in the microvasculature of fast-twitch muscle, where PO 2 during contractions is lower (8,47), since the reduction of NO 2 Ϫ to NO is augmented as PO 2 declines (14). This might explain why NO 3 Ϫ supplementation has been shown to preferentially distribute blood flow toward (24), and increase microvascular PO 2 within (26), the more fatiguesusceptible fast-twitch muscle fibers in rats and to speed phase II V O 2 kinetics when a greater proportion of fast-twitch muscle fibers are likely to be recruited (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies have shown that NO 3 Ϫ supplementation can increase muscle blood flow in the running rat (24) and that NO 2 Ϫ infusion can increase blood flow in humans performing forearm exercise (16). The potential for enhanced perfusion with BR is likely to be more pronounced in the microvasculature of fast-twitch muscle, where PO 2 during contractions is lower (8,47), since the reduction of NO 2 Ϫ to NO is augmented as PO 2 declines (14). This might explain why NO 3 Ϫ supplementation has been shown to preferentially distribute blood flow toward (24), and increase microvascular PO 2 within (26), the more fatiguesusceptible fast-twitch muscle fibers in rats and to speed phase II V O 2 kinetics when a greater proportion of fast-twitch muscle fibers are likely to be recruited (12).…”
Section: Resultsmentioning
confidence: 99%
“…Subjects completed one severe-intensity step test on days 4,5,8, and 9 of each dietary condition (PLA and BR). The same pedal cadence (either 35 or 115 rpm) was applied on days 4 and 5 of the supplementation period with the other cadence applied on days 8 and 9 of the supplementation period.…”
Section: Methodsmentioning
confidence: 99%
“…14 Given that the reduction of NO 2 -to NO is potentiated with decreasing O 2 tension van Faassen et al 2009) and that PO 2 is lower in type II compared to type I muscle (Behnke et al 2003;McDonough et al 2005), increasing plasma [NO 2 -] via NO 3 -supplementation may enhance NO 2 --derived NO synthesis and thus performance during exercise at higher intensities. We have previously reported a fall in plasma [NO 2 -] during high-intensity intermittent exercise following NO 3 -supplementation (Wylie et al 2013a;Thompson et al 2015).…”
Section: The Effect Of Br On Performance During the Yoyo Ir1 Testmentioning
confidence: 99%
“…Cellular oxygen availability can be assessed in muscle of contrasting fiber types with phosphorescence quenching 9 or in intact working muscle with either nearinfrared spectroscopy 28 or 1 H magnetic resonance spectroscopy. 36,60 However, these methods lack specificity when measuring the dynamics of cellular oxygen consumption in a large muscle group during exercise.…”
Section: Introductionmentioning
confidence: 99%